Depth-dependent variations of sedimentary dissolved organic matter composition in a eutrophic lake: Implications for lake restoration. (February 2016) - Xu, Huacheng; Guo, Laodong; Jiang, Helong
Abstract: Dissolved organic matter (DOM) plays a significant role in regulating nutrients and carbon cycling and the reactivity of trace metals and other contaminants in the environment. However, the environmental/ecological role of sedimentary DOM is highly dependent on organic composition. In this study, fluorescence excitation emission matrix-parallel factor (EEM–PARAFAC) analysis, two dimensional correlation spectroscopy (2D–COS), and ultrahigh resolution electrospray ionization Fourier transform ion cyclotron resonance mass spectrometry (FT–ICR–MS) were applied to investigate the depth-dependent variations of sediment-leached DOM components in a eutrophic lake. Results of EEM–PARAFAC and 2D–COS showed that fluorescent humic-like component was preferentially degraded microbially over fulvic-like component at greater sediment depths, and the relative abundance of non-fluorescent components decreased with increasing depth, leaving the removal rate of carbohydrates > lignins. The predominant sedimentary DOM components derived from FT–ICR–MS were lipids (>50%), followed by lignins (∼15%) and proteins (∼15%). The relative abundance of carbohydrates, lignins, and condensed aromatics decreased significantly at greater depths, whereas that of lipids increased in general with depth. There existed a significant negative correlation between the short-range ordered (SRO) minerals and the total dissolved organic carbon concentration or the relative contents of lignins and condensed aromatics ( p  < 0.05), suggesting that SRO mineral sorption plays a significant role in controlling the composition heterogeneity and releasing of DOM in lake sediments. Higher metal binding potential observed for DOM at deeper sediment depth (e.g., 25–30 cm) supported the ecological safety of sediment dredging technique from the viewpoint of heavy metal de-toxicity. Graphical abstract: Highlights: Vertical change in sediment DOM was quantified by EEM–PARAFAC, 2D–COS, and FT–ICR–MS. Humic-like component could be preferentially degraded microbially over fulvic-like component. Relative abundance of carbohydrates, lignins and aromatics decreased with depth but not lipids. Short-range ordered mineral sorption highly influences the composition and release of DOM in sediment. Depth-dependent metal binding heterogeneity highlights the eco-safety of sediment dredging technique.